Solitary eccrine syringofibroadenoma: a case report showing papillary tubular adenoma-like features - Toshiyuki Yamamoto; Keiko Miura; Hiroo Yokozeki (Our Dermatology Online, 2016)
We herein describe a case showing eccrine syringofibroadenoma occurred on the dorsum of the right foot of a 46-year-old Japanese female. Histopathologic examination revealed anastomosing cords and strands of cuboidal epithelial cells extending from the epidermis to the upper dermis, with a number of well-defined ducts suggesting eccrine ductal origin. In addition, there were papillary tubular adenoma-like ductal structures lined by a few rows of epithelial cells with papillary projections into the lumen surrounded by fibrous stroma in the mid-dermis. It is of note that various histologic features showing different differentiation were seen in a single lesion of eccrine syringofibroadenoma.